Analisis Minat Konsumen Terhadap Produk yang Dipromosikan Melalui Media Sosial Facebook pada Remaja dan Dewasa di Wilayah Pedesaan Brebes Selatan, Rembang, dan Kudus Jawa Tengah - Rizki Nur Anisa; Sibthi Alfiatuni’ma; Raihan Al May Sany; Khairani Zikrinawati; Zulfa Fahmy (Universitas Katolik Widya Karya Malang, 2023)
The digitalization of the economy gave rise to a variety of e-commerce that rivaled and detracted from youth and adult consumers on Facebook. The purpose of this study was to analyze the interest of adolescent and adult consumers in products promoted through Facebook social media in the rural areas of South Brebes, Rembang and Kudus. 10 people were represented in each region consisting of 5 teenagers and 5 adults using a purposive sampling technique. Methods of data collection using observation and interviews with researchers as the main research instruments. The research was carried out in each of the designated rural areas. The data from this study were analyzed using inductive analysis techniques and data triangulation was carried out to ensure the validity of the data. The results of this study showed that the interest of rural adolescents and adults in products promoted through social media Facebook had differences in terms of objectives, types of products they were interested in, and types of interest. Teenagers are interested in beauty and fashion products with exploratory interest types, while adults are interested in products from daily necessities, household goods, to hobbies, with interest types including transactional, preferential, referential, explorative, and selling interests. Interest in selling is something that is interesting and different from other interests